GUIDELINES ON INTRODUCTION OF COERCIVE MEASURES OF MEDIATION IN CIVIL DISPUTES IN THAILAND - Butprom, Natthasit; Cholsaktrakul, Pornphet; Mahavinijchaimontri, Pratya (Academic Journal Phranakhon Rajabhat University, 2025)
The main objective of this research is to find out guidelines on the introduction of the coercive measures of mediation in civil disputes in Thailand. It is qualitative research by conducting documentary research and studying the comparison between the law of Thailand and the laws of the United States of America and Canada. According to the study, in the United States of America and Canadian Confederation, there is the coercive mediation in civil disputes by forcing the parties to go through the process of mediation in the disputes before filing a lawsuit to a law court. As for Thailand, there is no law to force the parties to go through the process of mediation before filing a lawsuit. According to the research outcome, in Thailand, the parties should be forced to go through the process of mediation in civil disputes before filing a lawsuit in the same way as those in the foreign countries. This process of mediation will provide the parties with an opportunity to have a discussion on a solution to the problem through an intermediary. If the parties are not forced to go through the process of mediation in the disputes, they are likely to refuse to go through the process of mediation, resulting that there is less chance to settle the disputes, and there will be a great number of lawsuits to be filed to a law court. This research has a suggestion that Section 20 ter of the Civil Procedure Code should be amended in order that the parties must go through the mediation in the disputes before filing a lawsuit to a law court